2006
DOI: 10.1128/mcb.26.2.448-456.2006
|View full text |Cite
|
Sign up to set email alerts
|

BS69, a Specific Adaptor in the Latent Membrane Protein 1-Mediated c-Jun N-Terminal Kinase Pathway

Abstract: We previously demonstrated that the Epstein-Barr virus-encoded latent membrane protein 1 (LMP1) potently activates the cellular c-Jun N-terminal kinase (JNK) pathway by sequentially engaging an unknown adaptor, TRAF6, TAB1/TAK1, and JNKKs. We now show that BS69, a MYND domain-containing cellular protein, is the missing adaptor that bridges LMP1 and TRAF6, as the MYND domain and a separate region of BS69 bind to the carboxyl termini of LMP1 and TRAF6, respectively. While LMP1 promotes the interaction between BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 56 publications
2
56
0
Order By: Relevance
“…BS69/ZMYND11 functions as an adaptor protein bridging LMP1 and TRAF6, a central upstream component in the activation of JNK and other pathways in response to interleukin 1 and bacterial lipopolysaccharide. Activation of TRAF6 by BS69/ZMYND11 appears to be independent of other TRAF6 interacting partners such as TRIF, IRAK1 and IRAK4 thus identifying a novel signalling pathway in EBV-infected cells (Wan et al, 2006). The MYND domain of BS69/ ZMYND11 is essential for direct interaction with LMP1.…”
Section: Rassf1mentioning
confidence: 96%
See 2 more Smart Citations
“…BS69/ZMYND11 functions as an adaptor protein bridging LMP1 and TRAF6, a central upstream component in the activation of JNK and other pathways in response to interleukin 1 and bacterial lipopolysaccharide. Activation of TRAF6 by BS69/ZMYND11 appears to be independent of other TRAF6 interacting partners such as TRIF, IRAK1 and IRAK4 thus identifying a novel signalling pathway in EBV-infected cells (Wan et al, 2006). The MYND domain of BS69/ ZMYND11 is essential for direct interaction with LMP1.…”
Section: Rassf1mentioning
confidence: 96%
“…Finally, the MYND-containing protein suppressin has been shown to inhibit cell-cycle entry (LeBoeuf et al, 1998). In addition to its role as a transcriptional corepressor, BS69/ZMYND11 is also essential in latent membrane protein 1 (LMP1)-mediated activation of the JNK pathway (Wan et al, 2006). LMP1 is one of nine latent viral antigens expressed in Epstein-Barr virus (EBV)-infected cells.…”
Section: Rassf1mentioning
confidence: 99%
See 1 more Smart Citation
“…In adenocarcinoma overexpression models, TRAF6 has been hypothesized to interact with LMP1 indirectly through TRADD and/or RIP binding to CTAR2 (reviewed in [20]. More recently BS69 has been described as a potential bridging molecule between LMP1 CTAR2 and TRAF6 [28]. In mouse B cell lines, TRADD does not detectably interact with CTAR2 [21].…”
Section: Lmp1mentioning
confidence: 99%
“…Our preliminary data suggest that protein modification, particularly one other than ubiquitination, participates in the degradation of BS69 (data not shown). This is consistent with the finding that high doses of TICAM-1 induce the activation of TRAF E3 ligases [11] and protein modification [12], though the mechanisms have yet to be determined.The previous reports have demonstrated that BS69 physically binds EBV-derived LMP1 and negatively regulates the canonical NF-kB activation by LMP1 [10,13]. Although the regulatory mode of LMP1 is reciprocal to that of TICAM-1, the extranuclear displacement of BS69 commonly occurs in polyI:C-and LMP1-activating pathways.…”
mentioning
confidence: 99%